2021
DOI: 10.11604/pamj.2021.39.180.28818
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of HIV-1 drug resistant mutations and virologic failure

Abstract: Introduction mutations are important by ensuring that the HIV-1 agent remains fit in the environment and evades drugs that are developed purposely to kill them. In Kenya, mutations conferring resistance to available ARVs have been reported in previous studies. However, there is a paucity of information on whether these previous studies have reported all mutations conclusively that confer resistance to available drugs leading to virologic failure. Therefore, this study was sought to identify the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In a study conducted in Kenya's Busia County 34 , majority of the patients with treatment resistance were on TDF + 3TC + EFV regimen. Although majority of the patients on HAART in both this study and in the country were on this regimen, both the current study and the one conducted in Busia still reported a higher treatment failure rate for this cohort of HIV infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Kenya's Busia County 34 , majority of the patients with treatment resistance were on TDF + 3TC + EFV regimen. Although majority of the patients on HAART in both this study and in the country were on this regimen, both the current study and the one conducted in Busia still reported a higher treatment failure rate for this cohort of HIV infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Actionable interventions to improve these conditions will benefit Kenya in holding the reigns of increasing VLNS and DR. Many researchers have delved into the threat of HIV DR in Kenya [ 35 , 36 ]. However, little work has been done to actively identify poorly performing locations to tackle HIV DR. Our fast and effective method based on routinely collected data can identify poorly performing locations and accelerate the administrative processes in managing VLNS and HIV DR.…”
Section: Discussionmentioning
confidence: 99%
“…Although many anti-HIV drugs were developed for acquired immunodeficiency syndrome, it is still a global health problem ( 18 ). Therefore, it is important to further understand the molecular mechanisms of virus replication and the possible targets and mechanisms of virus inhibition.…”
Section: Discussionmentioning
confidence: 99%